Valuation through Narrative Intelligibility - Patrycja Kaszynska (Valuation Studies, 2023)
Narrative intelligibility is central to making sense of valuation. Narrative intelligibility is a framing device that combines empirical observation and situated interaction with teleological, purpose-oriented, normative inquiry. Thus understood, narrative intelligibility provides a useful analytical frame to explain how the phenomenon of valuation is practised. At the same time – and on the level of research – it bridges synthetically different traditions of thought, including actor–network theory’s descriptive accounts of valuation practices and humanities-grounded, normative theories of value. As such, narrative intelligibility offers a way of avoiding the alleged weakness of overstating the agency of devices and material actors in actor–network informed approaches, without however seeking to relocate analysis into the ‘ineffable’ realm of purely theoretical constructs, the way some humanities scholars are said to have done. The argument shows that the humanities-derived understanding of values, approached in terms of standards of justification and norms of criticism, can be combined with the vernacular concepts of valuation from actor–network theory in a way that promises a unified research agenda going forward.